ANALISIS BIOMASSA DAN CADANGAN KARBON BAMBU TALI (Gigantochloa apus Kurz.) DI HUTAN RAKYAT DESA SIRPANG SIGODANG KECAMATAN PANEI, KABUPATEN SIMALUNGUN - Sihol Marito Malau; Muhdi Muhdi; Irawati Azhar (Peronema Forestry Science Journal, 2016)
Forests absorb CO2 during photosynthesis and store it as organic matter in biomass plants, as well as bamboo plantations. This study aimed  to : (1) analysis biomass and carbon stock (2) obtain a model Allometric estimation of carbon stocks in vegetation potential of oil palm plantations in North Sumatra; (3) obtain the potential carbon stocks in forest conversion to bamboo plantations in North Sumatra. This research was conducted in Forest Community Sirpang Sigodang Village, Subdistrict, Simalungun District. The research was carried out in two stages, namely the first stage were to data in the field and the second stage was analyze of carbon biomass and plant in the laboratory. Parameters measured in the field was wet weight, whereas in the laboratory is measured moisture content, volatile matter content, ash content and carbon content. Carbon plants in the plot were determined using allometric models bamboo carbon rods. Models the relationship between plant biomass or carbon rods with dimensions created with a method that describes the relationship Allometric biomass or carbon mass per plant as a function of the diameter. The results showed that the best model of allometric equations for estimating biomass and carbon mass of bamboo plantations was W= 81.324+22.411D+1.710D2 and C=45.979+12.792D+0.973D2 (W=biomass; C=carbon mass; D= diameter), resulting in biomass and carbon mass of tali bamboo plants respectively were 10.91 ton/ha and 5.49 ton C/ha. Keywords: Bambu tali (Gigantochloa apus Kurz)., Community Forest, biomass analisys, carbon stock, Sirpang Sigodang Village.